Direct cerebello-striatal loop in dystonia as a possible new target for deep brain stimulation: A revised view of subcortical pathways involved - Kaji, Ryuji (Frontiers in Neurology, 2022)
Dystonia is the second most common movement disorder next to tremor, but its pathophysiology is unsettled. Its therapeutic measures include anti-cholingerics and other medications, botulinum neurotoxin injections, and stereotaxic surgery including deep brain stimulation (DBS), but there still remain a number of patients resistant to the therapy. Evidence has been accumulating that basal ganglia in association with the cerebellum are playing the pivotal role in the pathogenesis. Clinical observations such as sensory trick and the effects of muscle afferent stimulation and its blockage suggest the conflict between the cortical voluntary motor plan and the subcortical motor program or motor subroutine controlling the intended action semi-automatically. In this review, the current understanding of the possible pathways or loops involved in dystonia is presented, and we review promising new targets for DBS including the cerebellum.